Attributing Liability for Autonomous Vehicles: EU Multi-Level Approaches and Implications for Vietnamese Law - Dao, Phuc G. (Review of European and Comparative Law, 2026)
Autonomous Vehicles (AVs) call into question the driver-centered premises of road traffic liability, as the task of driving becomes a distributed, socio-technical process involving software, sensors, updates, connectivity, infrastructure, and (sometimes) remote supervision. This article offers a doctrinal comparative analysis of how liability can be attributed across three axes, civil, administrative, and criminal, when accidents occur where there are higher levels of automation. It argues that the European Union does not (and need not) rely on a single AV liability code. Instead, EU law combines an insurance-first, victim-compensation logic with the modernization of product liability for software-enabled harms and a risk-based regulatory style that imposes documentation, post-market, and safety-management duties on upstream actors. Using Germany, France, and the Netherlands as illustrative models, the article maps Vietnamese law through the same framework. It shows that Vietnam already embodies a strong victim-protection baseline through strict "source of extraordinary danger" doctrines and is developing more stringent product responsibility tools. At the same time, Vietnam faces persistent mismatch risks in evidentiary access, cyber incident attribution, and the calibration of criminal accountability. The article concludes with a direction of reform, modified as appropriate for Vietnam, that preserves rapid compensation while structuring recourse, data governance, and controlled piloting.